Endothelial Cell TGF-β (Transforming Growth Factor-Beta) Signaling Regulates Venous Adaptive Remodeling to Improve Arteriovenous Fistula Patency. Issue 7 (5th May 2022) - Taniguchi (谷口良輔), Ryosuke; Ohashi (大橋雄一), Yuichi; Lee (이중석), Jung Seok; Hu (胡海地), Haidi; Gonzalez, Luis; Zhang (张惟常), Weichang; Langford, John; Matsubara (松原裕), Yutaka; Yatsula, Bogdan; Tellides, George; Fahmy, Tarek M.; Hoshina (保科克行), Katsuyuki; et al.
Abstract : Background: Arteriovenous fistulae (AVF) are the gold standard for vascular access for hemodialysis. Although the vein must thicken and dilate for successful hemodialysis, excessive wall thickness leads to stenosis causing AVF failure. Since TGF-β (transforming growth factor-beta) regulates ECM (extracellular matrix) deposition and smooth muscle cell (SMC) proliferation—critical components of wall thickness—we hypothesized that disruption of TGF-β signaling prevents excessive wall thickening during venous remodeling. Methods: A mouse aortocaval fistula model was used. SB431542—an inhibitor of TGF-β receptor I—was encapsulated in nanoparticles and applied to the AVF adventitia in C57BL/6J mice. Alternatively, AVFs were created in mice with conditional disruption of TGF-β receptors in either SMCs or endothelial cells. Doppler ultrasound was performed serially to confirm patency and to measure vessel diameters. AVFs were harvested at predetermined time points for histological and immunofluorescence analyses. Results: Inhibition of TGF-β signaling with SB431542-containing nanoparticles significantly reduced p-Smad2–positive cells in the AVF wall during the early maturation phase (days 7–21) and was associated with decreased AVF wall thickness that showed both decreased collagen density and decreased SMC proliferation. SMC-specific TGF-β signaling disruption decreased collagen density but not SMC proliferation or wall thickness. Endothelial cell–specific TGF-β signaling disruption decreased both collagen density and SMC proliferation in the AVF wall and was associated with reduced wall thickness, increased outward remodeling, and improved AVF patency. Conclusions: Endothelial cell–targeted TGF-β inhibition may be a translational strategy to improve AVF patency.